Long-term inflation outcomes after hyperinflation: theory and evidence - Guerrero, Federico (2005)
This paper shows cross-country evidence that indicates that countries that have experienced hyperinflation display significantly lower long-term rates of inflation than countries that lack the same experience. A model to rationalize the main result is also presented. The suggested explanation for the documented empirical regularity is that hyperinflations reduce the social costs of increasing the collection of conventional taxes relative to the collection of seignorage by showing the downsides of resorting to the printing press in a crystal-clear way.